Balneotherapy in dermatology and rheumatology: a systematic review - Kiereta, Kacper; Cichowska, Zuzanna; Chmielowiec, Laura; Wacławek, Katarzyna; Janawa, Kamil; Ciesielka, Anna; Bacik, Małgorzata; Rechcińska, Aleksandra; Głodowska, Klaudia; Rdzanek, Bartłomiej Józef; Żelazo, Jakub (Quality in Sport, 2025)
Objective: Article’s aim is to characterize what a balneology is, what it consists of. To picture actual usage of balneotherapy in different fields of medicine; its possibilities and restrictions. Methods: A vast literature review was conducted using PubMed database. Reviewed articles included systematic reviews, randomized controlled trials, observational studies and meta-analyses. Keywords included “balneology”, “balneotherapy”, “peloid baths”, “water baths”, “balneotherapy dermatology”, “balneotherapy rheumatology”. Conclusions: Although balneotherapy might be considered as antiquated and according to some physicians, not scientifically proven, is efficient in reducing symptoms of some dermatological and rheumatological conditions due to its anti-inflammatory, keratolytic, antimicrobial, analgesic and myorelaxant effects. Albeit its role as complement therapy, it can achieve very good results alleviating pain and reducing amount of painkillers used, extending periods of remission or quality of live and well-being improvement.